Creating an Educational the Private Cloud Based on Simulation and User Interaction in Solving Educational Problems - Kovalev, Eugene; Kovaleva, Natalia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The authors proposes to create a single platform solution that combines social networking, crowdsourcing management system and knowledge management system and learning management. The optimal approach in this case may be private educational cloud deployments. In a study conducted information modeling the main processes of interaction between participants in the educational cloud. The authors also has been proposed criteria for evaluating the effectiveness of the resulting solutions, technological and organizational requirements.
Keywords: social networks; crowdsourcing management; knowledge management system; private educational cloud